Development of Value-Added Products from Sago Frond - M. N., Ahmad; Nurazureen, Matnin; Dayang Salwani, Awang Adeni; Kopli, Bujang (i-CATS University College, 2023)
Sago frond is the compound leaf of the palm Metroxylon sagu. Our earlier studies revealed that this material can be harnessed to produce Sago Frond Sugar (SFS), which contains cellobiose and glucose as the main sugars at about 10g/L and 5g/L, respectively. SFS has been proven as the comprehensive fermentation medium in production of L-lactic acid using Lactococcus lactis IO-1. The yield and productivity of L-lactic acid from SFS is comparable to the Standard Medium (even when amended with yeast extract) at 0.85g/g and 85%, respectively. SFS can be purified using Powdered Activated Charcoal (PAC) to produce Purified Sago Frond Sugar (PSFS) and has been shown to have antibacterial properties against several foods related bacteria. Cellobiose from sago frond was perceived to be beneficial as an antifungal agent when tested against Candida which is a common cause of skin infection, where the growth of C. tropicalis is highly affected by SFS. However, this purification process distinctly reduces its antifungal properties. In our attempt to increase the sugar concentration (hence the enzymatic activities), SFS was heated to yield 50% and 100% sugar concentrations. However, these too reduce its antifungal effect drastically by 20% and 0%, respectively. Sago frond sap, the liquid obtained by pressing freshly de-skinned sago fronds on a roller press machine, has been fermented to produce ethanol using the yeast Saccharomyces cerevisiae. The sap contains a higher amount of sugar (25 g/L) compared to SFS (15 g/L). It was observed that sterilised SFS exhibited cell growth of up to 90% of the yeast biomass. Astonishingly, similar growth was obtained when raw (unsterilized) sap was used as the fermentation medium. This confirmed our conclusion that sago frond sap can be used directly as the medium in large-scale ethanol fermentation without the need for sterilisation. Recently, sago frond has also been utilised for the production of silage as animal fodder. A combination of leaves and frond fibres can generate 42 tons of silage from the harvesting of approximately 500 sago logs, every day. In our preliminary trials, the best practice is to mix shredded sago leaves with sago frond sap which enhances the lactate fermentation using Lactococcus lactis IO-1 to produce nutritious silage. L. lactis IO-1 was recycled as the inoculant to increase the fermentation efficiency and quality of sago frond silage.